2013
DOI: 10.1089/scd.2012.0375
|View full text |Cite
|
Sign up to set email alerts
|

Induced Pluripotency and Oncogenic Transformation Are Related Processes

Abstract: Induced pluripotent stem cells (iPSCs) have the potential for creating patient-specific regenerative medicine therapies, but the links between pluripotency and tumorigenicity raise important safety concerns. More specifically, the methods employed for the production of iPSCs and oncogenic foci (OF), a form of in vitro produced tumor cells, are surprisingly similar, raising potential concerns about iPSCs. To test the hypotheses that iPSCs and OF are related cell types and, more broadly, that the induction of pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
85
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 104 publications
(86 citation statements)
references
References 60 publications
(86 reference statements)
0
85
0
1
Order By: Relevance
“…[2][3][4][5][6][7][8][9][10][11] Nonetheless, the striking similarity of the molecular features shared between iPS cell generation and tumorigenesis is providing key mechanistic insights on how CSC could actually arise, in some cases, from differentiated cells through a process of "pathological nuclear reprogramming." [12][13][14][15][16][17][18][19][20][21] A proof-of-concept demonstration of the close association between acquisition of stem cell properties by induced pluripotency and CSC-driven tumorigenesis has been recently carried out in a landmark study, showing that transient in vivo expression of reprogramming factors generates tumors with altered epigenetic states which cause abnormal growth of incompletely reprogrammed cells. 22 Though these findings are the first to confirm that premature termination of induced pluripotency can result in cancer development, it should be noted that oncogenic-transformed cells and iPS cells generated from common parental fibroblasts have been found to represent highly related, yet distinct, cell types based on expression profiling,share common "cellular ancestors" that develop along an equivalent molecular pathway(s) before they diverge.…”
Section: Metabolic Control Of Cancer Cell Stemness: Lessons From Ips mentioning
confidence: 99%
See 2 more Smart Citations
“…[2][3][4][5][6][7][8][9][10][11] Nonetheless, the striking similarity of the molecular features shared between iPS cell generation and tumorigenesis is providing key mechanistic insights on how CSC could actually arise, in some cases, from differentiated cells through a process of "pathological nuclear reprogramming." [12][13][14][15][16][17][18][19][20][21] A proof-of-concept demonstration of the close association between acquisition of stem cell properties by induced pluripotency and CSC-driven tumorigenesis has been recently carried out in a landmark study, showing that transient in vivo expression of reprogramming factors generates tumors with altered epigenetic states which cause abnormal growth of incompletely reprogrammed cells. 22 Though these findings are the first to confirm that premature termination of induced pluripotency can result in cancer development, it should be noted that oncogenic-transformed cells and iPS cells generated from common parental fibroblasts have been found to represent highly related, yet distinct, cell types based on expression profiling,share common "cellular ancestors" that develop along an equivalent molecular pathway(s) before they diverge.…”
Section: Metabolic Control Of Cancer Cell Stemness: Lessons From Ips mentioning
confidence: 99%
“…Indeed, a model comparing malignant transformation and (non-malignant) nuclear cell reprogramming demonstrated that differentiated cells should first acquire epigenetic changes that lead to a downregulation of the differentiation machinery, which is paralleled by an activation of glycolysis and other metabolic pathways. 15 Crucially, only then are the oncogenic or the pluripotent phenotypes fully acquired, depending on other stimuli such as stemness factors. Moreover, whereas reprogrammed pluripotent stem cells can acquire oncogenic traits, the converse is not true because oncogenic cells cannot acquire the bona fide pluripotent state possessed by stem cells.…”
Section: Metabolic Control Of Cancer Cell Stemness: Lessons From Ips mentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanisms underlying the reprogramming process are not well understood yet; however the three main transcription factors Oct4, Sox2 and Nanog, called master regulators of pluripotency, have proved responsible for maintaining the undifferentiated state. Basically both processes, reprograming and transformation, need the expression or activation of oncogenes (expression of Oct4, Sox2 and Nanog has been repeatedly observed in tumors), inactivation of tumor suppressor genes, overriding the senescence and apoptotic barriers and both processes also involve epigenetic changes and a metabolic switch towards a glycolytic metabolism [3,4]. The tumor suppressor p53 poses a barrier for pluripotency induction [5].…”
Section: Editorialmentioning
confidence: 99%
“…Recentemente, Riggs et al (2013) avaliaram a semelhança entre iPS e foco oncogênico e constataram que, apesar de tipos celulares diferentes, os processos de indução de pluripotência e de indução de tumor são processos relacionados.…”
Section: Pluripotência Versus Tumorigêneseunclassified